Porous electrode and preparation method thereof
By using the porous electrode formed by the acid etching conductive agent, the pore disappearance and destructive laser etching problems in the increase in pore volume of the lithium-ion battery cell are solved, and the effects of high energy density and fast charging are achieved.
Patent Information
- Application Number
- CN202411740793.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-21
AI Technical Summary
When existing lithium-ion batteries improve porosity, there are problems such as pore disappearance, laser etching destructiveness and complex processes, which are difficult to meet the needs of high energy density and fast charging.
Using an acid etching conductive agent, an acid etching conductive agent with several holes on the tube wall is formed by reacting the porous conductive agent in a strong acid, and mixing it with the active material and the binder to form a porous electrode.
The pore stability of the porous electrode is achieved, the risk of lithium electrodes is reduced, and the fast charging performance and energy density of the secondary battery are improved.
Smart Images

Figure CN119673945A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a porous electrode and a preparation method thereof. Background Art
[0002] In the field of lithium-ion battery technology, with the vigorous development of the electric vehicle industry and the country's vigorous promotion of new energy, the market's requirements for battery performance are increasing, especially in terms of endurance and safety. Lithium-ion batteries have been widely used in various electronic devices and electric vehicles due to their excellent energy density, long life and environmental protection characteristics. However, with the advancement of electric vehicle technology, more stringent requirements are placed on the energy density and fast charging capabilities of lithium-ion batteries. Among the many factors that improve the energy density of battery cells, thick coating technology occupies an important position. However, with the increase of coating surface density, the dynamic performance of the battery cell will drop sharply, which is contrary to the mainstream development direction of current power battery fast charging technology. Therefore, it has become particularly urgent to solve the problem of thick coating dynamics.
[0003] Improving the porosity of the pole piece is one of the key ways to solve the problem of thick coating dynamics. At present, the main methods to improve the porosity of the pole piece include adding pore formers to the slurry and laser etching the pole piece after rolling. However, these methods have obvious defects: after adding pore formers, the pores are easy to disappear during the rolling process, resulting in poor results; and the laser etching method is destructive to the pole piece, which may deteriorate the performance of the battery cell, and the process requirements are high, which is easy to lead to an increase in the defective rate and increase costs in actual production.
[0004] Conductive agents are key components in the positive and negative electrodes of batteries. Their main function is to reduce the internal impedance of the battery. Existing patented technology (CN202411012987.9) uses medium carbon powder to grow on a substrate to form a hollow porous electrode, and applies it to fuel cells to improve mass transfer efficiency. However, this technology only improves the longitudinal mass transfer efficiency, and the process is complicated, which is not suitable for large-scale application in lithium batteries.
[0005] In view of the above-mentioned defects of the existing porous electrode technology, technical personnel in this field urgently need a new technical solution to solve the above-mentioned problems, improve the performance of lithium-ion batteries, and meet the market demand for high energy density and fast charging capability. Summary of the invention
[0006] The purpose of the present invention is to provide a porous electrode with higher ionic conductivity, which can also make the distribution of alkali metal ions in the electrode more uniform, reduce the risk of lithium plating in the electrode, and thus improve the fast charging performance of the secondary battery.
[0007] In order to achieve this object, the present invention provides the following scheme:
[0008] A porous electrode comprises a current collector and an active material layer arranged on at least one surface of the current collector, wherein the active material layer comprises an active material, a binder and an acid-etched conductive agent; wherein the acid-etched conductive agent comprises at least one of an acid-etched carbon nanotube and an acid-etched carbon fiber; a tube wall of the acid-etched conductive agent is provided with a plurality of pores, the pore diameter of the pores is 1 to 5 nm, and the porosity of the acid-etched conductive agent is 60 to 70%.
[0009] Preferably, the aspect ratio of the acid-etched conductive agent is 60-200, and the tube diameter is 500nm-2μm. Preferably, the conductivity of the porous electrode is ≥5.4s / cm, and the membrane resistance is less than or equal to 3.601Ω.
[0010] Preferably, the power density of the porous electrode is ≥50w / kg.
[0011] Preferably, the porosity of the porous electrode is ≥40%.
[0012] The present invention also provides a method for preparing a porous electrode, comprising the following steps:
[0013] Step 1: Disperse the porous conductive agent in a strong acid, react at 45-60° C. for 6-12 hours to obtain an acid-etched conductive agent;
[0014] Step 2: Evenly mix the acid-etched conductive agent, active material and binder to obtain electrode slurry; and coat the electrode slurry on a current collector to obtain a porous electrode.
[0015] Preferably, in step 1, the ratio of the porous conductive agent to the strong acid is 0.4-0.6 g: 45-55 ml.
[0016] Preferably, in step one, the porous conductive agent includes at least one of carbon nanotubes and carbon fibers.
[0017] Preferably, in step 1, the strong acid includes at least one of nitric acid and sulfuric acid.
[0018] Preferably, the mass fraction of the nitric acid is 68%, and the mass fraction of the sulfuric acid is 98%.
[0019] The present invention also provides a secondary battery, comprising a diaphragm, an electrolyte, a battery shell and the above-mentioned electrode.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1) The porous electrode of the present invention uses an acid-etched conductive agent, so the pores of the porous electrode are stable and not easy to disappear, the manufacturing process is simple, the cost is low, and there is no need for laser etching to form holes in the prior art or adding pore-forming agents to form holes in the electrode preparation, which will not have a negative impact on the electrode itself.
[0022] 2) The surface of the acid-etched conductive agent of the present invention has a plurality of holes after acid etching, and these holes can facilitate the free entry and exit of alkali metal ions in the acid-etched conductive agent, thereby improving the ion transmission rate in the porous electrode.
[0023] 3) The acid-etched conductive agent of the porous electrode of the present invention is evenly dispersed in the electrode piece in different directions, which can not only improve the ion transmission capacity of the electrode piece in the longitudinal direction, but also promote the ion transmission in the lateral direction, so as to make the distribution of alkali metal ions in the electrode piece more uniform, reduce the risk of metal precipitation on the surface of the electrode piece, and thus improve the fast charging performance of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A schematic diagram of a porous electrode structure according to an embodiment of the present invention;
[0025] Figure 2 Schematic diagram of the acid-etched conductive agent structure according to one embodiment of the present invention.
[0026] Among them, 1. current collector; 2. active material layer; 21. acid-etched conductive agent; 211. pores. DETAILED DESCRIPTION
[0027] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] According to a first aspect of the present invention, a porous electrode is provided, comprising a current collector 1 and an active material layer 2 arranged on at least one surface of the current collector 1, wherein the active material layer 2 comprises an active material, a binder and an acid-etched conductive agent 21; wherein the acid-etched conductive agent 21 comprises at least one of an acid-etched carbon nanotube and an acid-etched carbon fiber; a tube wall of the acid-etched conductive agent 21 is provided with a plurality of pores 211, the pore diameter of the pores 211 is 1 to 5 nm, and the porosity of the acid-etched conductive agent 21 is 60 to 70%.
[0029] There are several holes 211 on the surface of the acid-etched conductive agent 21 after acid etching. These holes 211 can facilitate the free entry and exit of alkali metal ions in the acid-etched conductive agent 21, thereby improving the ion transmission rate in the porous electrode. The porous conductive agent is dispersed in a strong acid, and the tube wall is etched to obtain several holes 211. The pore size of the hole 211 is 1 to 5 nm, for example, 1 nm, 1.5 nm, 2, 2 nm, 5, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, and the porosity of the acid-etched conductive agent 21 is 60 to 70%, for example, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%. When the carbon nanotubes are subjected to acid etching, if the etching is too much, its structure may be damaged. Therefore, the present application limits the aperture of the hole 211 on the tube wall of the acid-etched conductive agent 21. When the aperture on the tube wall is within this range, the tubular structure of the acid-etched conductive agent 21 will not be destroyed, and there will still be several holes after acid etching. These holes can facilitate the free entry and exit of alkali metal ions in the acid-etched conductive agent 21, thereby improving the ion transmission rate in the porous electrode.
[0030] The porous electrode of the present invention uses an acid-etched conductive agent 21, and the pores of the porous electrode are stable and not easy to disappear. The manufacturing process is simple and the cost is low. It does not require laser etching to form holes in the prior art or adding pore-forming agents to form holes in the electrode preparation, and will not have a negative impact on the electrode itself.
[0031] The acid-etched conductive agent 21 of the porous electrode is evenly dispersed in the electrode in different directions, which not only improves the longitudinal ion transmission capacity, but also promotes the lateral ion transmission, making the distribution of alkali metal ions in the electrode more even, reducing the risk of metal precipitation on the surface of the electrode, thereby improving the fast charging performance of the secondary battery.
[0032] In one embodiment of the present invention, the aspect ratio of the acid-etched conductive agent 21 is 60-200, for example, 60, 615, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150; the tube diameter is 500nm-2μm.
[0033] In one embodiment of the present invention, the conductivity of the porous electrode is ≥5.4s / cm, and the membrane resistance is less than or equal to 3.601Ω. When the porous electrode has a lower resistance value, the current conduction efficiency can be significantly improved, so that the device responds to the current more quickly, thereby improving the overall performance; it can also reduce the heat generated during the current transmission process, thereby reducing the unnecessary loss of energy and improving the energy efficiency of the device; it helps to ensure the long-term stable operation of the product and reduce the risk of failure caused by excessive resistance.
[0034] In one embodiment of the present invention, the power density of the porous electrode is ≥50w / kg. The porous electrode of the present application can improve the power density of the pole piece. Electrodes with high power density usually mean higher production efficiency because more energy conversion or storage tasks can be completed in a shorter time. The material usage of the electrode can be reduced while ensuring performance, thereby reducing production costs; it also has better durability and stability, thereby extending the service life of the entire device.
[0035] In one embodiment of the present invention, the porosity of the porous electrode is ≥40%.
[0036] In one embodiment of the present invention, the current collector 1 is generally a structure or part for collecting current. The current collector 1 can be any material suitable for use as a secondary battery current collector 1 in the art, such as aluminum foil, copper foil, nickel foil, stainless steel or carbon material.
[0037] In one embodiment according to the present invention, when the porous electrode is the positive electrode, the active material may include but is not limited to layered oxide positive electrode materials, spinel structure positive electrode materials, olivine structure positive electrode materials, and polyanion positive electrode materials; the layered oxide positive electrode materials include lithium nickel oxide (such as lithium nickel oxide), lithium cobalt oxide (such as lithium cobalt oxide LiCoO2), nickel cobalt manganese oxide (such as NCM), nickel cobalt aluminum oxide (such as NCA), etc.; the spinel structure positive electrode material includes lithium manganese oxide (LiMn2O4); the olivine structure positive electrode material includes lithium iron phosphate (LiFePO4); the polyanion positive electrode material includes phosphates and sulfates.
[0038] When the porous electrode is a negative electrode, the active material may be one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium, etc. The graphite may be selected from one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material may be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites and silicon alloys; the tin-based material may be selected from one or more of elemental tin, tin oxide compounds and tin alloys.
[0039] In a second aspect of the present invention, a method for preparing a porous electrode is also provided, comprising the following steps:
[0040] Step 1: Disperse the porous conductive agent in a strong acid, react at 45-60° C. for 6-12 hours, and obtain an acid-etched conductive agent 21;
[0041] Step 2: Evenly mix the acid-etched conductive agent 21, the active material and the binder to obtain an electrode slurry; and coat the electrode slurry on the current collector 1 to obtain a porous electrode.
[0042] In one embodiment of the present invention, in step one, the reaction temperature of the porous conductive agent dispersed in the strong acid is 45-60°C, for example, it can be 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C; the reaction time is 6-12h, for example, it can be 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h, 12h.
[0043] The reaction time of the porous conductive agent and the strong acid should be within this range. If the porous conductive agent is heated in a strong acid solution for too long or at too high a temperature, or the acid concentration is too high and is not neutralized or treated in time, the porous conductive agent may be broken into smaller fragments due to excessive oxidation, or may even be completely oxidized into gases such as carbon dioxide, resulting in complete destruction of the structure. If the porous conductive agent is heated in a strong acid solution for too short a time, the aperture of the hole 211 of the acid-etched conductive agent 21 tube wall does not reach the scope of this application, and thus the ion transmission capacity of the porous electrode in the longitudinal direction cannot be improved, making the distribution of alkali metal ions in the pole piece more uniform, reducing the risk of metal precipitation on the pole piece surface, and improving the purpose of fast charging performance of the secondary battery.
[0044] When performing acid etching treatment on porous conductive agents, it is necessary to strictly control conditions such as acid concentration, treatment time and temperature to avoid unnecessary damage to the structure of the porous conductive agent. At the same time, it is also necessary to use appropriate testing methods (such as Raman spectroscopy, X-ray diffraction, etc.) to evaluate the structural changes of the porous conductive agent before and after treatment to ensure that the treatment effect meets expectations.
[0045] If the porous conductive agent is not properly handled during the acid etching process, its structure may be destroyed. Therefore, it is necessary to operate carefully and strictly control the conditions during the relevant treatment.
[0046] In one embodiment of the present invention, in step 1, the ratio of the porous conductive agent to the strong acid is 0.4-0.6 g: 45-55 ml, for example, 0.4 g: 45 ml, 0.4 g: 46 ml, 0.4 g: 47 ml, 0.4 g: 48 ml, 0.4 g: 49 ml, 0.4 g: 50 ml, 0.4 g: 51 ml, 0.4 g: 52 ml, 0.4 g: 53 ml, 0.4 g: 54 ml, 0.4 g: 55 ml, 0.5 g: 45 ml, 0.5 g: 46 ml, 0.5 g: 47 ml , 0.5g: 48ml, 0.5g: 49ml, 0.5g: 50ml, 0.5g: 51ml, 0.5g: 52ml, 0.5g: 53ml, 0.5g: 54ml, 0.5g: 55ml, 0.6g: 45ml, 0.6g: 46ml, 0.6g: 47ml, 0.6g: 48ml, 0.6g: 49ml, 0.6g: 50ml, 0.6g: 51ml, 0.6g: 52ml, 0.6g: 53ml, 0.6g: 54ml, 0.6g: 55ml. If the porous conductive agent is not handled properly during the acid etching process, its structure may be destroyed. Therefore, it is necessary to operate with caution and strictly control the conditions when carrying out the relevant treatment.
[0047] In one embodiment of the present invention, in step 1, the porous conductive agent includes at least one of carbon nanotubes and carbon fibers, wherein the carbon nanotubes may be single-walled carbon tubes or multi-walled carbon tubes; and the carbon fibers may be CNF or VGCF.
[0048] In one embodiment according to the present invention, in step 1, the strong acid includes at least one of nitric acid, sulfuric acid and hydrochloric acid.
[0049] In one embodiment of the present invention, the mass fraction of nitric acid is 68%, and the mass fraction of sulfuric acid is 98%. If the acid concentration is too high and is not neutralized or treated in time, the porous conductive agent may be broken into smaller fragments due to excessive oxidation, resulting in complete destruction of the structure, thereby failing to improve the ion transmission capacity of the porous electrode in the longitudinal direction, making the distribution of alkali metal ions in the pole piece more uniform, reducing the risk of metal precipitation on the pole piece surface, and improving the fast charging performance of the secondary battery.
[0050] In a third aspect of the present invention, a secondary battery is provided, comprising a separator, an electrolyte, a battery casing and the above-mentioned porous electrode.
[0051] The separator can be selected from various separators used in lithium ion batteries known to those skilled in the art, such as polypropylene microporous membrane, polyethylene felt, glass fiber felt or ultrafine glass fiber paper;
[0052] The secondary battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.
[0053] The present invention will be further described below by means of specific examples.
[0054] Example 1
[0055] Preparation of porous electrodes:
[0056] Step 1: Take 0.5g of carbon nanotubes and disperse them in 50mL of 98% concentrated sulfuric acid, react at 50°C for 9h to obtain an acid-etched conductive agent 21 with the carbon nanotube surface etched; wherein the aspect ratio of the carbon nanotubes is 90 and the tube diameter is 1μm.
[0057] Step 2: Prepare electrode slurry by stirring acid-etched conductive agent 21, CMC, SBR and graphite, and coat the slurry on the current collector 1 to obtain a porous negative electrode; wherein the average pore size on the tube wall of the acid-etched conductive agent 21 is 3nm, and the porosity of the acid-etched conductive agent 21 is 65%.
[0058] Preparation of lithium-ion batteries:
[0059] The separator, the positive electrode sheet and the negative electrode sheet are interlaced and then packaged with an aluminum-plastic film to prepare a battery cell, which is placed in a battery shell, an electrolyte is added, and then sealed to obtain a lithium-ion battery. Among them, the active material of the positive electrode sheet is lithium iron phosphate; the separator is a polyethylene-ceramic composite separator; the electrolyte salt of the electrolyte is lithium hexafluorophosphate, and the solvent is ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 1:2:1, and the electrolyte concentration is 1 mol / L.
[0060] Example 2
[0061] Different from Example 1, in the second step of preparing the porous electrode, the acid etching conductive agent 21, PVDF, SP, and lithium iron phosphate are stirred to prepare a slurry, and the slurry is coated on the current collector 1 to obtain a porous positive electrode;
[0062] The rest are the same as in Example 1 and will not be described again here.
[0063] Comparative Example 1
[0064] Different from Example 1, the conductive agent used in the negative electrode is carbon nanotubes that have not been acid-treated;
[0065] The rest are the same as in Example 1 and will not be described again here.
[0066] Table 1 shows the data of Examples 1 to 5 and Comparative Examples 2 to 7, and the rest is the same as Example 1 and will not be described again.
[0067] Table 1
[0068]
[0069]
[0070] Performance Test:
[0071] The conductive agents of Examples 1 to 5 and Comparative Examples 1 to 7 were tested for porosity and film resistance, and the test results are shown in Table 2;
[0072] The lithium ion batteries of Examples 1 to 5 and Comparative Examples 1 to 7 were subjected to electrochemical performance tests. The test results are shown in Table 2.
[0073] Table 2
[0074]
[0075] As shown in Table 2, by comparing the experimental data of Example 1 and Comparative Example 1, it can be seen that the data of Example 1 is better than that of Comparative Example 1, which shows that the porous electrode of the present invention uses an acid-etched conductive agent 21, the pores are stable and not easy to disappear, and there are a number of holes on the surface of the acid-etched conductive agent 21 after acid etching. These holes can facilitate the free entry and exit of alkali metal ions in the acid-etched conductive agent 21, reduce the membrane resistance of the electrode piece, and improve the ion transmission rate in the porous electrode; it can also make the distribution of alkali metal ions in the electrode piece more uniform, reduce the risk of metal precipitation on the surface of the electrode piece, thereby improving the fast charging performance of the secondary battery.
[0076] Comparing the experimental data of Example 1 with those of Comparative Examples 2-3, it can be seen that the data of Example 1 is better than those of Comparative Examples 2-3, indicating that when the ratio of the porous conductive agent to the strong acid exceeds the range specified in the present invention, the structure of the porous conductive agent will be destroyed, and the acid-etched conductive agent 21 with a plurality of holes in the tube wall cannot be formed, thereby failing to improve the various performances of the electrode sheet.
[0077] Comparing the experimental data of Example 1 and Comparative Examples 4 to 7, it can be seen that the data of Example 1 is better than those of Comparative Examples 4 to 7, indicating that if the porous conductive agent is heated in a strong acid solution at too high a temperature or for too long, the porous conductive agent may be broken into smaller fragments due to excessive oxidation, or may even be completely oxidized into gases such as carbon dioxide, resulting in complete destruction of the structure, and thus failing to improve the various properties of the electrode sheet. If the porous conductive agent is heated in a strong acid solution for too short a time or at too low a temperature, the aperture of the pores 211 of the acid-etched conductive agent 21 tube wall will not be within the scope of this application, and thus failing to improve the ion transmission capacity of the porous electrode in the longitudinal direction, making the distribution of alkali metal ions in the electrode sheet more uniform, reducing the risk of metal precipitation on the electrode sheet surface, and improving the fast charging performance of the secondary battery.
[0078] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A porous electrode, characterized in that: It includes a current collector and an active material layer arranged on at least one surface of the current collector, wherein the active material layer includes an active material, a binder and an acid-etched conductive agent; wherein the acid-etched conductive agent includes at least one of acid-etched carbon nanotubes and acid-etched carbon fibers; the tube wall of the acid-etched conductive agent is provided with a plurality of holes, the pore diameter of the holes is 1 to 5 nm, and the porosity of the acid-etched conductive agent is 60 to 70%.
2. The porous electrode according to claim 1, characterized in that The aspect ratio of the acid-etched conductive agent is 60-200, and the tube diameter is 500nm-2μm.
3. The porous electrode according to claim 1, characterized in that The electrical conductivity of the porous electrode is ≥5.4s / cm, and the membrane resistance is less than or equal to 3.601Ω.
4. The porous electrode according to claim 1, characterized in that The power density of the porous electrode is ≥50w / kg.
5. The porous electrode according to claim 1, characterized in that: The porosity of the porous electrode is ≥40%.
6. A method for preparing a porous electrode, characterized in that: The following steps are involved: Step 1: Disperse the porous conductive agent in a strong acid, react at 45-60°C for 6-12 hours to obtain an acid-etched conductive agent; Step 2: Evenly mix the acid-etched conductive agent, active material and binder to obtain electrode slurry; and coat the electrode slurry on a current collector to obtain a porous electrode.
7. The method for preparing a porous electrode according to claim 6, characterized in that: In the step 1, the ratio of the porous conductive agent to the strong acid is 0.4-0.6 g: 45-55 ml.
8. The method for preparing a porous electrode according to claim 6, characterized in that: In the step 1, the porous conductive agent includes at least one of carbon nanotubes and carbon fibers.
9. The method for preparing a porous electrode according to claim 6, characterized in that: In the step 1, the strong acid includes at least one of nitric acid and sulfuric acid.
10. The method for preparing a porous electrode according to claim 9, characterized in that: The mass fraction of the nitric acid is 68%, and the mass fraction of the sulfuric acid is 98%.
Citation Information
Patent Citations
A hollow multi-level ordered porous electrode and a preparation method and a battery
CN118538926B